MANAJEMEN SARANA DAN PRASARANA PENDIDIKAN ISLAM SEBAGAI FAKTOR PENDUKUNG MUTU PEMBELAJARAN: KAJIAN LITERATUR - Sidki, Ahmad; Suklani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The management of Islamic educational facilities and infrastructure plays a strategic role in supporting the quality of learning in educational institutions. Well-managed facilities and infrastructure can create a conducive learning environment and support the achievement of Islamic educational objectives. This article aims to examine the role of managing Islamic educational facilities and infrastructure as a supporting factor for learning quality based on previous studies. The research method employed is a literature review by analyzing scientific journal articles and relevant references published over the last five years. The results indicate that effective management of facilities and infrastructure, including planning, procurement, utilization, maintenance, and supervision, significantly contributes to improving learning quality. Optimal management enhances the effectiveness of the learning process, learning comfort, and the motivation of both students and educators. Therefore, strengthening the management of Islamic educational facilities and infrastructure is essential as an integral effort to sustainably improve learning quality.